Analisis Kandungan Asam Benzoat dan Kalium Sorbat Dalam Minuman yang Diproduksi UMKM di Bali Selatan Periode 2025 - Sugijanto, Milyadi; Rahmadinha, Vallina; Devyantari, Ni Kadek; Waisnawi , Putu Ayu Gaudiya; Dewi , Ni Luh Kade Arman Anita (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
Bali is one of the world’s tourist destinations that drives the growth of Micro Small and Medium Enterprise (MSME) industries, including the traditional beverage sector. Traditional beverages are generally produced naturally without the addition of preservatives. However, to extend shelf life and maintain product safety until it reaches consumers, some producers add preservatives. Excessive use of preservatives may pose health risks. The aims of the study are to analyze the content of benzoic acid and potassium sorbate as preservatives in beverages produced by MSMEs in South Bali during the 2025 period. The research employed descriptive cross-sectional design with both qualitative and quantitative analyses using High Performance Liquid Chromatography. The study samples consisted of 22 beverage products produced by MSMEs in Bali. All samples were analyzed to identify the presence and levels of benzoic acid and sodium sorbate. The results showed that none of the 22 beverage samples contained benzoic acid or sodium sorbate. Therefore, it can be concluded that the MSME beverages examined during this period did not contain these preservatives.